2019
DOI: 10.1007/s10851-019-00922-y
|View full text |Cite
|
Sign up to set email alerts
|

Forward Stability of ResNet and Its Variants

Abstract: The residual neural network (ResNet) is a popular deep network architecture which has the ability to obtain high-accuracy results on several image processing problems. In order to analyze the behavior and structure of ResNet, recent work has been on establishing connections between ResNets and continuoustime optimal control problems. In this work, we show that the post-activation ResNet is related to an optimal control problem with differential inclusions, and provide continuous-time stability results for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…The difference between the ResNet and the ordinary network is that the jump connection is introduced, which can help the information of the previous residual block flow into the next residual block without obstruction. The problem of vanishing gradient and degradation caused by too deep a network is avoided [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the ResNet and the ordinary network is that the jump connection is introduced, which can help the information of the previous residual block flow into the next residual block without obstruction. The problem of vanishing gradient and degradation caused by too deep a network is avoided [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of more Mish activation functions can improve the representation ability of ResNet. The bottleneck residuals module of different layers for the ResNet-50 architecture is expressed in Figure 2 [ 58 , 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, this increase can also raise several problems, including the vanishing of information between the distant layers during training. Recent work has shown that CNNs can be substantially deeper, more accurate, and efficient to train, if they contain shortcut connections between distant layers [36].…”
Section: The Densenet Neural Architecturementioning
confidence: 99%
“…Otherwise, the results would not be acceptable. The well-known networks, for instance, AlexNet [25], variants of ResNet [26], VGG [27], GoogLeNet [28], EfficientNet [29], and DensNet [30] prove themselves to be powerful in many applications; however, a major drawback to them is that they usually require significant training time, causing a high cost in real-world applications [31].…”
Section: Introductionmentioning
confidence: 99%